PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS MEDIA DIGITAL BAGI GURU SMP/MTS DI KOTA SAMARINDA - Putra, Firnanda Pradana; Hafidzah, Anisa; Toni, Toni (Universitas Pattimura, 2026)
Mathematics education in the 21st century is closely related to the development of digital technology, which is expected to attract students' interest in learning, help them understand mathematical concepts, and achieve more optimal learning. This community service program aims to provide assistance to junior high school/MTs mathematics teachers so that they can produce digital-based learning media products. The service method uses ABCD by managing and utilizing the assets, strengths, and potential of teachers, students, and schools in developing digital media-based mathematics learning. The steps taken in this service are 1) Discovery by analyzing the conditions of teachers, 2) Dream with the hope of realizing interactive digital media-based mathematics learning that has an impact on students in the classroom. In this case, teachers can create digital media in the form of digital student worksheets using Live Worksheets and Canva, create test questions using Wordwall, discussion forums using Padlet, and present geometry and algebra images using Geogebra. 3) Design by designing a community service model in the form of assistance in several stages, 4) Define by fixing the schedule for assistance activities, and 5) Destiny by implementing the fixed community service design based on the analysis of conditions. The results of the community service carried out for junior high school/MTs mathematics teachers in Samarinda City showed that teachers were able to create digital media-based learning media in the form of Geogebra, Canva, digital worksheets or live worksheets, Wordwall, and Padlet. In addition, teachers can apply digital media created in mathematics learning in the classroom. Digital media created using free and easily accessible applications, either offline or online, using devices such as mobile phones, laptops, or computers/PCs.